A new kind of high-explosive bombs of huge power - Golodyaev, Alexander I. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This article is about the latest explosive devices, not secret ones, since patents are public. Nowadays there are hydrides of various metal and alloys, capable of bonding and releasing hydrogen. Under certain conditions, the release process is of an avalanche type and occurs in a form of a „physical“ explosion. The paper deals with the method of providing conditions for the avalanche-type release. The method of obtaining necessary parameters of hydrides is described as well as the tendencies in the development of explosive devices.